Lech’s Supposed Origins in Croatia: Regarding the Identification of the Rivers Huy and Krupa in the Works of Jan Długosz and Maciej of Miechów - Kekez, Hrvoje (Kwartalnik Historyczny, 2019)
The present article is a further contribution to the debate on the famous late medieval and early Renaissance narrative of the legendary origins of the Poles. The paper focuses on the legendary castle of ‘Psary’ — the ‘ancestral home’ of Prince Lech, that is on the geographical information given by chroniclers Jan Długosz and Maciej of Miechów in their writings. The author dismisses the identification of ‘Psary’ with Krapina or Pharos (Starigrad on the island of Hvar), arguing that ‘Psary’ was the medieval Minor Pset most likely located on top of Pušačko Hill (Pušačko brdo) in the vicinity of the late medieval castle Krupa (present-day Bosanska Krupa in Bosnia and Herzegovina).